Relationship between the 2D:4D ratio, physical performance variables, and body composition in elite wrestling athletes - Méndez Rodríguez, J. P.; Montenegro Arjona, O. A.; Monterrosa Quintero, A. (Retos: nuevas tendencias en educación física, deporte y recreación, 2024)
Background: The 2D:4D ratio in various sports has revealed significant relationships between this digit indicator and sports performance, but few studies have focused on elite wrestlers. Thus, the present study has two main objectives: firstly, to present descriptive data comparing it between genders, and secondly, to identify significant correlations with the 2D:4D ratio. Methods: A total of 22 wrestlers participated in the study, and their anthropometric variables, bilateral 2D:4D ratio, muscle power (CMJ), isometric traction strength, and handgrip strength were compared. Results: The findings show significant correlations between the right 2D:4D ratio and residual mass (r = .46; p < .05); Z-Score transverse thorax (r = .61; p < .01); inversely with ectomorphy (r = -.46; p < .05) and handgrip strength (r = .43; p = .042); and the left 2D:4D with Z-Score chest girths (r = .45; p < .05) and Z-Score weight (r = .43; p = .042). Conclusions: It is concluded that the 2D:4D ratio could be a predictive indicator of body composition components as well as a measure of handgrip strength performance and respiratory capacity in Olympic wrestling athletes.